The Usefulness of Common IVY (Hedera helix L.) Extracts Against Bacterial and Fungal Pathogens Found in Local Hospitals: Uses of Hedera helix L. for Bacterial and Fungal Disease (Biological Sciences - PJSIR, 2022)
The current study was carried out to highlights the antibacterial and antifungal activity of Hedera helix L. by using its different fractions. Both activities were carried out under agar well diffusion method, while for fractions obtaining the cold maceration method was followed which were tested against four fungal species including Fusarium oxysporum, Aspergillus flavors, P. pallidum and Alternaria alternate and four bacterial strains, Staphylococcus aureus, Streptococcus mutans, Serratia marcescens and Methicillin resistance, Staphylococcus aureus. The fractions which were extracted from the Hedera helix shown different zone of inhibition (ZOI) against both the fungal and bacterial strains. Chloroform and n-hexane extracted samples showed the highest antifungal activity against Polyspondylium pallidum with complete inhibition zone and the least activity was shown by an aqueous fraction. In the antibacterial activity, the crude methanolic extracts have shown the highest inhibition zone (46-57%) against the selected bacterial strains, while the lowest activity was reported from aqueous fractions (21-26%). The other fractions moderately inhibit the growth of the selected strains but were significant.